Analisis Pengelolaan Obat di UPTD Puskesmas Singandaru Kota Serang Banten - Candra Junaedi; Hasna Dewi; Mujianto Mujianto (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Drug management in community health centers is important, especially at the planning and procurement stages. Ineffective drug management impacts health centers both medically and economically. The aim is to determine drug management at the UPTD Puskesmas Singandaru by Permekes No. 74 Tahun 2016 and other relevant literature. Method: Observational research with a cross-sectional design. Primary data was taken through interviews and secondary data from drug management data. The samples used are pharmaceutical supplies. Research instruments include LPLPO, RKO, SBBK, and in-depth interview guide sheets. Data analysis is descriptively guided by Permekes No. 74 Tahun 2016 and other relevant literature. Results: The planning suitability indicator is 93% appropriate, the procurement indicator for the available budget for drug purchasing needs is 65% and the BMHP is 35%, the suitability of demand and receipt of drugs is 38% not yet appropriate (100% standard) because there are empty drugs in the gudang farmasi kabupaten kota, storage and distribution indicators of 100% are relevant, as well as recording and reporting indicators of 100% but reporting for Psychotropics and Narcotics is still managed by the Dinas Kesehatan Kota.